EDUKASI PEMBERIAN ASI EKSKLUSIF DENGAN STATUS GIZI BAYI USIA 4-12 BULAN DI WILAYAH KERJA PUSKESMAS KOTO BARU KABUPATEN DHARMASRAYA TAHUN 2024 - Husna; Nabila Alfina; Novia Dwijayanti (LPPM Universitas Ekasakti, 2024)
Exclusive breast milk is breast milk given to babies from birth for 6 months, without adding and/or replacing it with other foods or drinks. The aim of this research is to identify exclusive breastfeeding for babies aged 4-12 months in the work area of ??the Koto Baru Community Health Center, Dharmasraya Regency. In this research method, the researcher used analytical observational with a cross sectional approach. The population of this study was all mothers and babies aged 4-12 months in the working area of ??the Koto Baru Community Health Center, Dharmasraya Regency, totaling 68 babies. The sample in this study was a portion of mothers and babies from the population of all mothers and babies aged 4-12 months in the working area of ??the Koto Baru Community Health Center, Dharmasraya Regency, totaling 40 babies. The data collection technique uses probability sampling. The results of 40 respondents, the majority, namely 24 respondents (60.0%) had poor nutritional status, 40 respondents, the majority, namely 25 respondents (62.5%) did not give exclusive breast milk to their babies. Discussion Breast milk is the main food for babies which is very beneficial. Breast milk fulfills 100% of the baby's needs up to 6 months of age, whereas at the age of 4-12 months it only fulfills 60% of the baby's needs, so there is a need for complementary foods for breast milk. Breast milk contains various nutrients needed for the growth and development of babies. Solid food is given after the child is 6 months old and breastfeeding is continued until 2 years. The conclusion is that the majority of babies aged 4-12 months in the Koto Baru Health Center Working Area, Dharmasraya Regency are not given exclusive breast milk. There is education between giving exclusive breastfeeding and the nutritional status of babies aged 4-12 months in the Koto Baru Health Center Working Area, Dharmasraya Regency.